Feel Good or Be Happy: Distinctions Between Emotions and Development in the Environmental Psychology Research of Wellbeing - Ernst-Montenegro, R (Taylor and Francis, 2017)
This chapter explores that environmental psychology has assimilated these approaches with the objective of contributing to the explanation of the relationship between human and physical environments. Environmental psychology was born in the 1960s in the face of increasing attention to the urban challenges caused by population growth, which meant that researchers in the new field focused on people’s interactions with the built environment. Psychological theories are often used to study wellbeing in environmental psychology. The chapter provides a review of critical perspectives that underlie the epistemological and methodological assumptions of community environmental psychology research. Critical approaches in environmental psychology had to overcome the limitations imposed by the prevailing political approaches to environmental and institutional issues, as well as concerns about citizen participation. Some studies in environmental psychology have examined the process of social construction of relations with the environment. Studies in environmental psychology have explicitly addressed the critical analysis of environmental problems, which is found more frequently in sociology. © 2018 selection and editorial matter, Nicholas J. L. Brown, Tim Lomas, Francisco Jose Eiroa-Orosa; individual chapters, the contributors.